The Implementation of The Pracerja Card Program in Improving the Quality of Public Services in The City of Cirebon - Mawa Rizky, Cindy Octa; Rohida, Leni (Syntax Literate, 2026)
One of the government's innovations to enhance citizens' competencies and improve the quality of digital-based public services is the implementation of the Kartu Prakerja Program. However, several challenges emerged in the City of Cirebon, including limited access to information, complex registration procedures, and uneven levels of training effectiveness. Using the Service Quality (SERVQUAL) indicators developed by Parasuraman, Zeithaml, and Berry (1988)—namely tangibles, reliability, responsiveness, assurance, and empathy—this study examines how the implementation of the Kartu Prakerja Program contributes to improving public service quality. The research employs a qualitative approach through observations, in-depth interviews, and document analysis. The findings indicate that program implementation performs relatively well in terms of assurance and reliability, particularly with regard to process transparency and service certainty. However, due to insufficient technical assistance and diverse participant needs, the responsiveness and empathy dimensions remain limited. Substantively, the digital platform is perceived to enhance service efficiency, although constraints in digital literacy pose significant challenges. The overall results suggest that the Kartu Prakerja Program has contributed to improving public service quality in the City of Cirebon, yet several aspects still require optimization. The recommendations include strengthening public outreach, expanding technical support, and improving the digital platform to better accommodate the needs of local communities